In Silico Design, Synthesis, and Evaluation of Novel Enantiopure Isoxazolidines as Promising Dual Inhibitors of α-Amylase and α-Glucosidase - Fahad Alhawday; Fahad Alminderej; Siwar Ghannay; Bechir Hammami; Abuzar E. A. E. Albadri; Adel Kadri; Kaiss Aouadi (Molecules, 2024)
Isoxazolidine derivatives were designed, synthesized, and characterized using different spectroscopic techniques and elemental analysis and then evaluated for their ability to inhibit both α-amylase and α-glucosidase enzymes to treat diabetes. All synthesized derivatives demonstrated a varying range of activity, with IC50 values ranging from 53.03 ± 0.106 to 232.8 ± 0.517 μM (α-amylase) and from 94.33 ± 0.282 to 258.7 ± 0.521 μM (α-glucosidase), revealing their high potency compared to the reference drug, acarbose (IC50 = 296.6 ± 0.825 µM and 780.4 ± 0.346 µM), respectively. Specifically, in vitro results revealed that compound 5d achieved the most inhibitory activity with IC50 values of 5.59-fold and 8.27-fold, respectively, toward both enzymes, followed by 5b. Kinetic studies revealed that compound 5d inhibits both enzymes in a competitive mode. Based on the structure–activity relationship (SAR) study, it was concluded that various substitution patterns of the substituent(s) influenced the inhibitory activities of both enzymes. The server pkCSM was used to predict the pharmacokinetics and drug-likeness properties for 5d, which afforded good oral bioavailability. Additionally, compound 5d was subjected to molecular docking to gain insights into its binding mode interactions with the target enzymes. Moreover, via molecular dynamics (MD) simulation analysis, it maintained stability throughout 100 ns. This suggests that 5d possesses the potential to simultaneously target both enzymes effectively, making it advantageous for the development of antidiabetic medications.